Textbook on Scar Management 2020
DOI: 10.1007/978-3-030-44766-3_53
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Technologies in Scar Management: Remodeling of Post-surgical Linear Scar Using Microplasma Radiofrequency

Abstract: Linear scar is a common problem in all fields of surgery as it leads to unpleasant appearance that is not socially acceptable. In particular, linear scars in the exposed areas such as face, neck, and upper extremities cause significant psychological disturbance to patients who need proper medical assistance to release their suffering. The author proposed tissue remodeling strategy on an existed linear scar using FMRT (fractional microplasma radiofrequency technology) to render gross view of a linear scar less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…This releases energy that causes slight epidermal ablation and creates controlled micro‐perforations that can reach the superficial dermis, promoting the regeneration and repair of the epidermis. Concurrently, the generated heat is conducted to the subcutaneous tissue, promoting the proliferation and reorganization of dermal collagen fibers, and initiating the body's wound healing mechanisms 18 . Previous studies have shown that microplasma radiofrequency combined with glucocorticoid injection in the treatment of hypertrophic scarring after early deep burns is effective, safe, and has a low incidence of adverse reactions 19 …”
Section: Discussionmentioning
confidence: 99%
“…This releases energy that causes slight epidermal ablation and creates controlled micro‐perforations that can reach the superficial dermis, promoting the regeneration and repair of the epidermis. Concurrently, the generated heat is conducted to the subcutaneous tissue, promoting the proliferation and reorganization of dermal collagen fibers, and initiating the body's wound healing mechanisms 18 . Previous studies have shown that microplasma radiofrequency combined with glucocorticoid injection in the treatment of hypertrophic scarring after early deep burns is effective, safe, and has a low incidence of adverse reactions 19 …”
Section: Discussionmentioning
confidence: 99%